PENGARUH PERILAKU KEUANGAN, SELF CONTROL, DUKUNGAN SOSIAL KELUARGA TERHADAP LITERASI KEUANGAN PADA SISWA SMA N 4 PADANG - Irma Andriani; Nikmatul Husna; Nelly Prima Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine the effect of financial behavior, self control, and family social support on financial literacy partially and simultaneously at SMA N 4 Padang. The data used is primary data using a questionnaire. The sampling technique used proportional random sampling with a sample size of 65 students. The technical analysis used is multiple regression and hypothesis testing. The results showed that there was a partial influence of financial behavior, self control, and social support on financial literacy at SMA N 4 Padang. And there is a simultaneous influence of financial behavior, self control, and social support on financial literacy at SMA N 4 PadangKeywords: family social support, financial literacy, financial behavior, self control.